Emotions and Family Interactions in Childhood: Associations with Leukocyte Telomere Length - Robles, Theodore F. (Psychoneuroendocrinology, 2015)
Conceptualizations of links between stress and cellular aging in childhood suggest that accumulating stress predicts shorter leukocyte telomere length (LTL). At the same time, several models suggest that emotional reactivity to stressors may play a key role in predicting cellular aging. Using intensive repeated measures, we tested whether exposure or emotional “reactivity” to conflict and warmth in the family were related to LTL. Children (N=39; 30 target children and 9 siblings) between 8 and 13 years of age completed daily diary questionnaires for 56 consecutive days assessing daily warmth and conflict in the marital and the parent-child dyad, and daily positive and negative mood. To assess exposure to conflict and warmth, diary scale scores were averaged over the 56 days. Mood “reactivity” was operationalized by using multilevel modeling to generate estimates of the slope of warmth or conflict scores (marital and parent-child, separately) predicting same-day mood for each individual child. After diary collection, a blood sample was collected to determine LTL. Among children aged 8-13 years, a stronger association between negative mood and marital conflict, suggesting greater negative mood reactivity to marital conflict, was related to shorter LTL (B = -1.51, p < .01). A stronger association between positive mood and marital affection, suggesting positive mood reactivity, was related to longer LTL (B = 1.15, p < .05). These effects were independent of exposure to family and marital conflict and warmth, and positive and negative mood over a two-month period. To our knowledge, these findings, although cross-sectional, represent the first evidence showing that links between children's affective responses and daily family interactions may have implications for telomere length.